Recruiting the public relations officer during British Colonial Malaysia - Syed Abdullah Idid, Syed Arabi; Arandas, Mohammed Fadel; Chang, Peng Kee (Centre for Postgraduate Studies, Infrastructure University Kuala Lumpur, 2016)
This is a study on the growth of public relations in Malaysia based on the advertisements placed in the newspapers during the colonial period. Tracing the historical development serves to make a better understanding about the nature of public relations practice. This paper therefore aims at exploring the development of the public relations profession by studying the advertisements placed in the nationwide newspapers, the Straits Times and the Singapore Free Press & Mercantile Advertiser from 1939 which included the early advertisement that contained the phrase “public relations” to 1956 a year before the independence of the Federation of Malaysia. An analysis of the advertisements was made to fully understand the historical development of public relations in Malaya or then Malaysia.